The future as a design problem - Stuart, Reeves; Murray, Goulden; Robert, Dingwall (MIT Press, 2016)
An often unacknowledged yet foundational problem for design is how ‘futures‘ are recruited for design practice. This problem saturates considerations of what could or should be designed. We distinguish two intertwined approaches to this: ‘pragmatic projection’, which tries to tie the future to the past, and ‘grand vision’, which ties the present to the future. We examine ubiquitous computing as a case study of how pragmatic projection and grand vision are practically expressed to direct and structure design decisions. We assess their implications and conclude by arguing that the social legitimacy of design futures should be increasingly integral to their construction.